Case Study Of Statistical Reasoning On Integrated Learning Needs Of Statistics In Comic Digital Teaching Materials - Gunadi, Farid; Dadang Junadi; Yaya S Kusumah; Dadan Dasari (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The low statistical reasoning ability of students and limited contextual learning media that are interesting and easy to understand are two of the weaknesses in learning statistics material. This study aims to examine students' statistical reasoning in the context of learning needs integrated with digital teaching materials, Statistics Comics. This study uses a case study approach involving high school students, teachers, and vice principals as subjects, as well as qualitative data analysis of the results of interviews with the three subjects. The results of the study, which were analyzed qualitatively with the help of Atlasti 8, showed that statistical reasoning learning requires a contextual and digital-based approach. This finding indicates that the development of digital teaching materials based on comics is needed as an innovative alternative in learning statistics that supports improving students' statistical literacy and reasoning in the digital era.